5-A STUDY ON CONSUMERS’ ADOPTION AND BEHAVIOURAL INTENTION TOWARDS INNOVATIVE BANKING PRODUCTS - (:unkn) unknown (My University, 2018)
There is a growing interest inthe concept of innovation. It can be seen that especiallyin banking sector banks have risen their technologicalinvestments, and have made various innovations in orderto facilitate, simplify and speed up their products,services and processes. Within this context, this study isaimed to analyze the factors affecting consumers’adoption towards innovative banking products, and theirrelations with consumer behavioural intention to useinnovative banking products. In this context, there wereconducted a survey with 235 MBA students who study atBahçeşehir University Graduate School of SocialSciences. It was determined that there are factors havingeffects on behavioural intention of consumers to useinnovative banking products. According to varianceanalysis, result show that there is no statisticallysignificant difference in the responses of participants’adoption factors towards innovative banking product andtheir behavioural intention according to demographicvariables.

İnovasyon kavramına ilgi giderek artmaktadır. Özellikle bankacılık sektöründe bankaların son yıllarda teknolojik yatırımlarını artırdıkları, ürünlerini, hizmetlerini ve süreçlerini kolaylaştırmak, basitleştirmek ve hızlandırmak üzere çeşitli inovasyonlar gerçekleştirdikleri görülmektedir. Bu çalışma çerçevesinde tüketicilerin inovatif bankacılık ürünlerine yönelik kabullerini etkileyen faktörler ve bu faktörlerin tüketici davranışsal niyeti üzerine etkisi belirlenecektir. Bu bağlamda, Bahçeşehir Üniversitesi Sosyal Bilimler Enstitüsü’nde öğrenim görmekte olan 235 MBA öğrencisi üzerinde bir çalışma gerçekleştirilmiştir. Katılımcıların inovatif bankacılık ürünlerine yönelik kabullerinin ve davranışsal niyetleri üzerinde etkisi olduğu belirlenmiştir. Gerçekleştirilen farklılık analizleri sonuçlarına göre katılımcıların inovatif bankacılık ürünlerine yönelik tüketici kabulünü etkileyen faktörlerin ve davranışsal niyetlerinin demografik değişkenlerine göre istatistiksel açıdan farklılaşmadığı tespit edilmiştir.
İNOVATİF BANKACILIK ÜRÜNLERİNE YÖNELİK TÜKETİCİ KABULÜ VE DAVRANIŞSAL NİYETİ ÜZERİNE BİR ARAŞTIRMA
Keywords: İktisat; Uluslararası İlişkiler; İşletme